Personal exposure to particulate matter and heart rate variability among informal electronic waste workers at Agbogbloshie: a longitudinal study - Afua A. Amoabeng Nti (BMC, 2021)
Abstract Background Informal electronic waste recycling activities are major contributors to ambient air pollution, yet studies assessing the effects or relationship between direct/continuous exposure of informal e-waste workers to particulate matter and cardiovascular function are rare. Methods Repeated measurements of fractions of PM2.5, PM10–2.5, and PM10 in personal air of informal e-waste workers, (n = 142) and a comparable group (n = 65) were taken over a period of 20 months (March 2017 to November, 2018). Concurrently, 5-min resting electrocardiogram was performed on each participant to assess resting heart rate variability indices. Linear mixed-effects models were used to assess the association between PM fractions and cardiac function. Results SDNN, RMSSD, LF, HF and LH/HF ratio were all associated with PM. Significant associations were observed for PM2.5 and Mean NN (p = 0.039), PM10 and SDNN (p = 0.035) and PM 10–2.5 and LH/HF (p = 0.039). A 10 μg/m3 increase in the concentrations of PM 2.5, PM10–2.5, and PM10 in personal air was associated with reduced HRV indices and increased resting HR. A 10 μg/m3 per interquartile (IQR) increase in PM10–2.5 and PM10, decreased SDNN by 11% [(95% CI: − 0.002- 0.000); (p = 0.187)] and 34% [(95% CI: − 0.002-0.001); (p = 0.035)] respectively. However, PM2.5 increased SDNN by 34% (95% CI: − 1.32-0.64); (p = 0.493). Also, 10 μg/m3 increase in PM2.5, PM10–2.5 and PM10 decreased RMSSD by 27% [(− 1.34–0.79); (p = 0.620)], 11% [(− 1.73, 0.95); (p = 0.846)] and 0.57% [(− 1.56–0.46); (p = 0.255%)]. Conclusion Informal e-waste workers are at increased risk of developing cardiovascular disease from cardiac autonomic dysfunction as seen in reduced HRV and increased heart rate.